2020
DOI: 10.1182/blood-2020-139534
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Hypoalbuminemia Predicts Inferior Outcome in Patients with Diffuse Large B-Cell Lymphoma

Abstract: Albumin at diagnosis can be used to predict survival in diffuse large B-cell lymphoma (DLBCL). But whether consecutive albuminemia, which seen in DLBCL patients from time to time, could be more accuracy to predict outcome remains unknown. We retrospectively analyzed 574 de novo DLBCL patients treated with R-CHOP from our and other 2 centers. All the patients were divided into a training cohort (n=278) and a validation cohort (n=296) depending on the source of the patients. Overall survival (OS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Sarcopenia is associated with shorter survival, reduced response to treatment, increased treatment‐related toxicities, frequent dose reduction, and early termination of treatment 13,24–27 . Hypoalbuminaemia is a predictive factor for shorter survival, decreased relative dose intensity of anthracycline and cyclophosphamide, and increased risk of TRM 28–32 . High NLR is also correlated with shorter survival, lower CR rate, advanced stage, higher LDH level, and increased risk of depression 32–37 .…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia is associated with shorter survival, reduced response to treatment, increased treatment‐related toxicities, frequent dose reduction, and early termination of treatment 13,24–27 . Hypoalbuminaemia is a predictive factor for shorter survival, decreased relative dose intensity of anthracycline and cyclophosphamide, and increased risk of TRM 28–32 . High NLR is also correlated with shorter survival, lower CR rate, advanced stage, higher LDH level, and increased risk of depression 32–37 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the physical status of the patient (poor performance status), tumour staging, etc. can also lead to hypoproteinemia 12 …”
Section: Discussionmentioning
confidence: 99%
“…can also lead to hypoproteinemia. 12 Hypoalbuminemia is a well-known finding related to cancer and is commonly regarded as a sign of malnutrition. Studies have shown that the incidence of hypoalbuminemia in cancer patients is about 20%-45.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Im Zusammenhang mit Globulin wurde Albumin außerdem in Form der Albumin-Globulin-Ratio (AGR) eine prognostische Aussagekraft bezogen auf das präoperativ chemotherapeutisch behandelte Rektum-Karzinom(Toiyama et al 2018) und das DLBCL(Kim et al 2018) zugeschrieben.Die im Rahmen dieser Arbeit erzielten Ergebnisse zeigen, dass ein SA < 3,5 g/dl für ältere Patienten mit DLBCL prognostisch relevant für das PFS und das OS ist. Damit konnten bisherige Ergebnisse aus der Literatur bestätigt werden: In einer retrospektiven Studie mit 124 DLBCL-Patienten mit einem Durchschnittsalter von 58 (20-84) Jahren war ein SA-Cutoff-Wert von 3,7 g/dl ebenfalls signifikant für OS und PFS(Dalia et al 2014), ebenso in einer bisher nur als Abstract veröffentlichten chinesischen Studie mit einem SA-Cut-off-Wert von 3,9 g/dl(Wei et al 2017). Von mehreren untersuchten Blutwerten war in einer retrospektiven Studie mit 157 DLBCL-Patienten allein SA prognostisch signifikant für das Gesamtüberleben(Bairey et al 2016).…”
unclassified